The Three Questions : Based on a Story by Leo Tolstoy - Tolstoy, Leo graf, 1828-1910. (New York : Scholastic Press, 2002)
Nikolai asks his animal friends to help him answer three important questions: "When is the best time to do things?" "Who is the most important?" and "What is the right thing to do?"
Keywords: Conduct of life -- Juvenile fiction; Animals -- Juvenile fiction